Nitrogen-fixing rhizobial strains isolated from Desmodium incanum DC in Argentina: Phylogeny, biodiversity and symbiotic ability - Toniutti, María Antonieta (2017)
Desmodium spp. are leguminous plants belonging to the tribe Desmodieae of the subfamily Papil-ionoideae. They are widely distributed in temperated and subtropical regions and are used as forageplants, for biological control, and in traditional folk medicine. The genus includes pioneer species thatresist the xerothermic environment and grow in arid, barren sites. Desmodium species that form nitrogen-fixing symbiosis with rhizobia play an important role in sustainable agriculture. In Argentina, 23 nativespecies of this genus have been found, including Desmodium incanum. In this study, a total of 64 D.incanum-nodulating rhizobia were obtained from root nodules of four Argentinean plant populations.Rhizobia showed different abiotic-stress tolerances and a remarkable genetic diversity using PCR fin-gerprinting, with more than 30 different amplification profiles. None of the isolates were found at morethan one site, thus indicating a high level of rhizobial diversity associated with D. incanum in Argentineansoils. In selected isolates, 16S rDNA sequencing and whole-cell extract MALDI TOF analysis revealedthe presence of isolates related to Bradyrhizobium elkanii, Bradyrhizobium japonicum, Bradyrhizobiumyuanmingense, Bradyrhizobium liaoningense, Bradyrhizobium denitrificans and Rhizobium tropici species.In addition, the nodC gene studied in the selected isolates showed different allelic variants.Isolates were phenotypically characterized by assaying their growth under different abiotic stresses.Some of the local isolates were remarkably tolerant to high temperatures, extreme pH and salinity,which are all stressors commonly found in Argentinean soils. One of the isolates showed high tolerance totemperature and extreme pH, and produced higher aerial plant dry weights compared to other inoculatedtreatments. These results indicated that local isolates could be efficiently used for D. incanum inoculation.